Design and validation of an assessment rubric of relevant competencies for employability - Sánchez-Ramírez, José Manuel; Íñigo-Mendoza, Victoria; Marcano, Beatriz; Romero-García, Carmen (Journal of Technology and Science Education, 2023)
This article highlights the importance of promoting relevant competencies for employability in vocational training students, while considering the demands of the globalized world. The objective was to design and validate an assessment rubric of relevant competencies for employability. Seven competencies were selected: problem-solving, teamwork, adaptive capacity, communication, creativity, leadership and decision-making. A rubric was designed in which three command levels were established: low, medium and high, along with their respective indicators. A content validation process was also used by means of expert judgement. Ten (10) expert judges were selected to carry out a quantitative and qualitative validation in three stages and the indicators were modified until Aiken’s V coefficients of ≥ 0.80 (p = 0.05) were obtained for all indicators of the established competencies. It is concluded that the rubric is valid enough to assess relevant competencies for employability in vocational training students.
Keywords: assessment rubrics; competencies; content validity; employability; Scopus